The Feasibility of Water Cycle Diorama Media Based on Quizizz Paper Mode to Improve Learning Outcomes of Fourth Grade Elementary School Students - Septiani Anggun Izzatus Solikhah; Sri Cacik (JURNAL PENDIDIKAN DASAR NUSANTARA, 2026)
This study aims to develop and test the feasibility of the Water Cycle Diorama Media Based on Quizizz Paper Mode to Improve the Learning Outcomes of Fourth Grade Students of UPT SDN Penambangan 3. The research method used is Research and Development (R&D) with the ADDIE model. The feasibility of the media was tested through expert validation. The validation results showed that this media was very feasible to use, with a validation score of 96%, media experts 96%, and language experts 94%. Practicality data was obtained from the results of the student response questionnaire totaling a score of 578 with an average percentage score of 96%, and the results of the teacher response questionnaire obtained a score of 48 with a percentage score of 96%. Effectiveness data from student test results analyzed using the N-Gain score formula, obtained an average result of 0.81. If the percentage figures are converted into effectiveness categories, it can be concluded that the Water Cycle Diorama Media Based on Quizizz Paper Mode falls into the "High" category. Thus, the Water Cycle Diorama Media Based on Quizizz Paper Mode can be used as an alternative effective learning media to improve the learning outcomes of fourth grade students at UPT SDN Penambangan 3.